Identifikasi Level Pengelolaan Tata Kelola SIPERUMKIM Kota Salatiga berdasarkan COBIT 2019 - Adila Safitri; Imam Syafii; Kusworo Adi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
SIPERUMKIM is the digitization process of public service licensing recommendations for housing implementation. The utilization of information technology governance is used to facilitate monitoring and evaluating the performance of SIPERUMKIM information technology which has been implemented in Housing and Settlement Area in Salatiga city. Information technology governance is a process that can manage investment decisions related to information technology within the company to achieve goals and meet company needs. The use of COBIT 2019 analysis in information technology governance aims to help organizations achieve risk optimization, governance, and information technology management. The results of this study are in the design form of corporate information technology governance and knowing the important process recommendations for the Department of Housing and Settlement of the City of Salatiga. These three important process recommendations are APO12, DSS02, and DSS03.